Comparative Outcomes Analysis of Single-Port versus Multi-Port Laparoscopic Right Hemicolectomy in Colon Cancer - Seyed Vahid Hosseini (Shiraz University of Medical Sciences, 2018)
Background: In recent years, single-port laparoscopic colectomy (SPLC) has been introduced as a new technique for colorectalsurgery. Despite several studies, available results are too sparse to accurately identify differences between SPLC and conventionalmultiport laparoscopic colectomy (MPLC). In a continuing effort, the aim of this study was to compare these two techniques in coloncancer patients.Methods: 76 patients with colon cancer who underwent either SPLC or MPLC took part in this study. Demographic data and complicationssuch as age, gender, operative time, hospital stay, intra-operative blood volume loss, and internal organ injury were assessed.The patients were followed up for 6 months. Statistical analysis was performed by SPSS software using Student’s t-test, Chi-squaretest, or Fisher’s exact test.Results: The complications were similar in both SPLC and MPLC groups. Operative time was significantly lower in SPLC (P = 0.003).No significant differences were observed in other factors (P > 0.05).Conclusions: According to studies conducted so far, it seems that the difference in the surgeon’s experience, types of the colorectaldiseases, and types of the colorectal resection may affect the outcomes like operative time and hospital stay. Therefore, furthercoherent investigations with larger datasets are essential for a detailed comparison.